Families today / Connie R. Sasses. - Sasse, Connie R. (New York : Glencoe/McGraw-Hill, 1997)
Units cover the family foundation, strengthening relationships, managing with insight, supporting family and friends, extending your relationships, growing as a person moving toward independence, and forming your own family.
Includes index.
Keywords: Families -- United States; Social change -- United States; Interpersonal relations -- United States